The role of brainstem biopsy and targeted therapies in pediatric diffuse midline glioma/diffuse intrinsic pontine glioma - Sheikh, Shehryar R.; Recinos, Violette M. R.; Thompson, Eric M.; Mangum, Ross; Wright-Nadkarni, Mariah; Gampel, Bradley; Patel, Neha J. (Frontiers in Oncology, 2024)
Pediatric diffuse midline glioma (DMG), including diffuse intrinsic pontine glioma (DIPG), are aggressive brainstem tumors with a dire prognosis, traditionally diagnosed based on MRI characteristics. The recognition that molecular characteristics may determine prognosis and response to therapy has led to a reevaluation of biopsy necessity. This comprehensive review addresses the evolving role of brainstem biopsies in diagnosing and managing these tumors – both within the context of a clinical trial and in routine clinical care. We examine practice variability around brainstem biopsies for DMG/DIPG, revealing a global inconsistency in biopsy application and perceptions amongst providers. We show that safety profiles from contemporary studies demonstrate a high diagnostic success rate with minimal permanent morbidity, supporting the feasibility of biopsies in expert centers. Beyond the safety angle, we discuss the utility of biopsies in enabling personalized medicine, highlighting how molecular profiling has been used in multiple centers to guide targeted therapies. We present initial evidence from case studies and registry reports to address whether these molecularly targeted approaches are 1) clinically feasible, and 2) likely to extend survival. Furthermore, we present evidence to support the notion that biopsies facilitate the design of more refined clinical trials, shifting from a one-size-fits-all model to molecularly stratified studies. We discuss how this new paradigm for trial design is likely necessary in the context of DMG/DIPG given the lack of progress in this disease for the last several decades. Future directions discussed in the review include liquid biopsy techniques to complement or replace tissue sampling, aiming to enhance diagnostic precision and treatment monitoring.